Investigating the Application and Distribution of Metadiscourse Features in Research Articles in Applied Linguistics between English Native Writers and Iranian Writers: A Comparative Corpus-based Inquiry - Farahani, Mehrdad Vasheghani (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
Metadiscourse features are the elements that can show the presence of writer(s) in the writing process. The main objective of the present study was to run a quantitative corpus-based study on the way metadiscourse features (elements) were used by English native writers and Iranian non-native writers in the field of Applied Linguistics. To this end, 29 articles in the field of Applied Linguistics written by native speakers of English and Iranian non- native speakers of English were randomly selected; compiling together a corpus of 173839 words. Also, for the raw data and corpus analysis, the Sketch engine software was exploited by the researcher. The results of the study couldreveal the fact that in overall, writers of both corpora made use of interactive metadiscourse features more than interactional metadiscourse ones and that the texts written by native speakers enjoyed more metadiscourse markers compared to texts written by Iranian non-native speakers.